2022
DOI: 10.3390/ijerph19127339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Social and Emotional Competence Enhancement Program for Adolescents Who Bully: A Quasi-Experimental Design

Abstract: Background: The purpose of this study was to develop a social and emotional competence enhancement (SECE) program as an intervention for adolescents who bully, and to investigate its effects on school bullying behavior and mental health. Methods: A pre–posttest, 1-month follow-up nonequivalent control group quasi-experimental design was used. In total, 71 school bullies were included in the analysis. Results: The effects of this program were significant with regard to group-by-time interaction effects on socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“… [ 40 ] Reduce negative effect of bullying Australia RCTs 31 adolescents aged 13–14 years Cyber Friendly Schools Program Mean pre-test: 0.26 Mean post-test: 0.33 p value: p = 0.012 Student bullying victimization and perpetration behavior Effectively reduce trauma of bullying 9. [ 41 ] Reduce negative effect of bullying and improve mental health South Korea Quasi experimental 71 students (mean age: 14.41) Social and Emotional Competence Enhancement Program Mean pre-test: 9.91 Mean post-test: 2.74 p value: p < 0.001 School Bullying Behavior Effectively reducing negative impact of bullying with improve social competence, emotional regulation, and empathy 10. [ 42 ] Reducing bullying behaviors and its negative impact China RCTs 189 students (mean age: 15.79) School-Based Mindfulness Intervention Mean pre-test: 1.49 Mean post-test: 1.09 p value: p <0.05 Chinese Version of the Olweus Bully/Victim Questionnaire (OBQ-CV) Effectively reducing negative impact of bullying and its incidence 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 40 ] Reduce negative effect of bullying Australia RCTs 31 adolescents aged 13–14 years Cyber Friendly Schools Program Mean pre-test: 0.26 Mean post-test: 0.33 p value: p = 0.012 Student bullying victimization and perpetration behavior Effectively reduce trauma of bullying 9. [ 41 ] Reduce negative effect of bullying and improve mental health South Korea Quasi experimental 71 students (mean age: 14.41) Social and Emotional Competence Enhancement Program Mean pre-test: 9.91 Mean post-test: 2.74 p value: p < 0.001 School Bullying Behavior Effectively reducing negative impact of bullying with improve social competence, emotional regulation, and empathy 10. [ 42 ] Reducing bullying behaviors and its negative impact China RCTs 189 students (mean age: 15.79) School-Based Mindfulness Intervention Mean pre-test: 1.49 Mean post-test: 1.09 p value: p <0.05 Chinese Version of the Olweus Bully/Victim Questionnaire (OBQ-CV) Effectively reducing negative impact of bullying and its incidence 11.…”
Section: Resultsmentioning
confidence: 99%
“…The first and last sessions are face-to-face individual counseling activities, whilst Sessions 2–9 are done in groups utilizing cognitive behavioral techniques. 41 Counseling is provided by psychiatric nurses by establishing a therapeutic connection that focuses on participants’ experiences of bullying at school, bullying motives, family dynamics, relationships with peers, unsolved challenges, decision-making patterns, and reflection. To boost participant focus, each session is bundled with pictures, video clips, and games.…”
Section: Resultsmentioning
confidence: 99%
“…Hasil dari studi ini memberikan bukti relativitas budaya dari dimesi Ei dan SEL dan mengindikasikan adanya hubungan antara dimensi EI dan SEL (Song & Kim, 2022) Mengembangkan program peningkatan kompetensi sosial dan emosional (SECE) sebagai intervensi bagi remaja yang melakukan perundungan, dan untuk menyelidiki dampaknya terhadap perilaku perundungan di sekolah dan kesehatan mental.…”
Section: Hasilunclassified
“…On the other hand, empirical studies have found that there is a negative correlation between students' SEC and bullying behavior (Du et al, 2018). SEC can help to reduce bullying-related behavior problems (Song & Kim, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, empirical studies have found that there is a negative correlation between students' SEC and bullying behavior (Du et al, 2018). SEC can help to reduce bullying‐related behavior problems (Song & Kim, 2022). Extensive studies have shown that effective mastery of SEC is associated with higher well‐being and better school performance.…”
Section: Introductionmentioning
confidence: 99%